Battery
By forming a stable and flexible SEI film in the battery, the problem of battery capacity decay caused by the volume expansion of silicon materials is solved, and the cycle stability and high-temperature long-cycle performance of the battery are improved.
Patent Information
- Application Number
- CN202511422155.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-06
- Publication Date
- 2026-01-09
AI Technical Summary
The volume expansion of silicon materials during charging and discharging causes repeated repair and regeneration of the SEI film, resulting in rapid capacity decay and deterioration of cycle performance.
By cooperating with the diaphragm and the electrolyte, a stable and flexible SEI film is formed. By controlling the number of small-diameter particles on the coating surface and the ratio of cyclic carbonates to fluoroethylene carbonates, the small-diameter particles are excessively swollen and corroded in the electrolyte, thus forming a stable and flexible SEI film.
This reduces the risk of SEI film rupture during silicon material expansion, and improves the cycle stability and high-temperature long-cycle performance of the battery.
Smart Images

Figure CN121307422A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of batteries, in particular to a battery. BACKGROUND
[0002] The traditional graphite negative electrode is limited by its inherent low theoretical capacity, and it is difficult to meet the growing demand for high-performance energy storage. In this context, silicon materials have attracted much attention due to their ultra-high theoretical specific capacity and suitable lithium intercalation potential. However, silicon materials have a significant volume effect during the charge and discharge process, with a volume expansion rate of 280%-300% compared to the initial volume. This dramatic structural change directly leads to the instability of the electrode-electrolyte interface.
[0003] During the cycle process, the solid-state electrolyte interface (SEI) film formed on the surface of the silicon-based negative electrode will bear a huge mechanical stress due to the periodic expansion / contraction of the silicon material during the charge and discharge process. When the stress accumulation exceeds the fracture toughness of the SEI film, the interface protection layer will break, exposing the fresh silicon surface. The newly exposed active material will continuously react with the electrolyte, inducing the repeated repair and regeneration of the SEI film. This dynamic process not only accelerates the irreversible consumption of active lithium and electrolyte, but also causes the cumulative rise of the interface impedance, ultimately leading to rapid capacity decay and rapid deterioration of cycle performance.
[0004] Therefore, it is very important to invent a battery with a SEI film structure that is highly stable and flexible. SUMMARY
[0005] To solve the problem in the prior art that the repeated repair and regeneration of the SEI film caused by the volume expansion of the silicon material leads to rapid capacity decay and rapid deterioration of cycle performance, the present application provides a battery. The battery of the present application can form a relatively stable and flexible SEI film on the surface of the negative electrode sheet through the synergistic cooperation of the separator and the electrolyte, thereby reducing the risk of SEI film damage during the expansion of the silicon-based material, improving the interface stability between the separator and the electrode sheet, reducing the high-temperature cycle impedance of the battery, and improving the high-temperature long cycle performance of the battery.
[0006] To achieve the above object, the present application provides a battery, which comprises a separator, a negative electrode sheet, a positive electrode sheet and an electrolyte; the separator comprises a carrier layer and a coating layer on both sides of the carrier layer, the coating layer corresponding to the negative electrode active layer in the negative electrode sheet is composed of first particles, and the coating layer corresponding to the positive electrode active layer in the positive electrode sheet is composed of first particles and second particles, the composition of the first particles comprises a first polymer, the first polymer is an ester group-containing polymer, and the number ratio of the primary particles of the first particles with a particle size less than or equal to 0.3 μm to the primary particles of the first particles in the area of 100 μm x 100 μm on the surface of the coating layer is 0.01% to 4%; the electrolyte comprises a cyclic carbonate and a fluoroethylene carbonate, and the weight ratio of the cyclic carbonate to the fluoroethylene carbonate is (0.2-1.5):1.
[0007] Compared with the prior art, the present application has at least the following advantages:
[0008] The battery of the present application can ensure that the trace amount of first particles in the separator, under the joint action of the cyclic carbonate and the fluoroethylene carbonate, can realize a high matching degree between the first particles and the cyclic carbonate and the fluoroethylene carbonate in the electrolyte, so that the small-particle-size first polymer particles can be excessively swollen under the action of the cyclic carbonate, the small-particle-size first particles after excessive swelling can be slightly dissolved due to corrosion by high content FEC, the small-particle-size first particles can dissolve a trace amount of first polymer and / or ester group-containing groups, and the cyclic carbonate and the fluoroethylene carbonate can jointly form a relatively stable and flexible SEI film on the surface of the negative electrode sheet, thereby reducing the risk of rupture of the SEI film during the expansion of the silicon material, improving the cycle stability of the battery, and at the same time improving the high-temperature adhesion between the separator and the electrode sheet, reducing the high-temperature cycle impedance of the battery, and improving the high-temperature long cycle performance of the battery.
[0009] Other features and advantages of the present application will be described in detail in the following specific embodiments.
[0010] The endpoints of the ranges and any values disclosed herein are not limited to the precise values stated. The ranges or values should be construed to be roughly around the ranges or values. For ranges, the endpoints are included between the values, and the endpoints are included with the single points, and the single points are included between the values. These ranges or values should be considered to be specifically disclosed herein. BRIEF DESCRIPTION OF DRAWINGS
[0011] Figure 1The image shown is one of the surface SEM images of the diaphragm of the present invention.
[0012] Figure 2 The image shown is a second SEM image of the surface of the diaphragm of the present invention. Detailed Implementation
[0013] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the invention. Unless otherwise specified herein, data ranges include endpoints.
[0014] It should be noted that the numerical designations such as "first" and "second" in this invention are only used to distinguish different substances or methods of use, and do not represent a difference in order.
[0015] This invention provides a battery comprising a separator, a negative electrode, a positive electrode, and an electrolyte. The separator includes a carrier layer and coatings located on both sides of the carrier layer. The coating corresponding to the negative active layer in the negative electrode is composed of first particles, and the coating corresponding to the positive active layer in the positive electrode is composed of first particles and second particles. The first particles comprise a first polymer, which is an ester-containing polymer. Within a 100μm × 100μm area on the surface of the coating, the particle size is less than or equal to 0.3μm (e.g., 0.3μm, 0.25μm, 0.2μm, 0.15μm, 0.1μm, 0.05μm, or 0.01μm). The number of primary particles in a single particle accounts for 0.01%-4% of the total number of primary particles in the first particle (e.g., 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, or 4%); the electrolyte comprises cyclic carbonate and fluoroethylene carbonate, wherein the weight ratio of the cyclic ethylene carbonate to the fluoroethylene carbonate is (0.2-1.5):1 (e.g., 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, or 1.5:1).
[0016] In the diaphragm, the coating can be located on one side of the carrier layer or on both sides of the carrier layer. When the coating is located on both sides of the carrier layer, the coatings on the two sides of the carrier layer can be the same or different.
[0017] In this invention, the first particle may include primary particles. The percentage of primary particles with a diameter less than or equal to 0.3 μm within a 100 μm × 100 μm area of the coating surface refers to the percentage of individual primary particles with a diameter less than or equal to 0.3 μm within a 100 μm × 100 μm area of the coating surface away from the carrier layer, based on the total number of all primary particles. Specifically, the following method can be used for testing: On the surface of the coating away from the carrier layer, arbitrarily select a 100μm×100μm area. It is understood that when the coating is discontinuous, a 100μm×100μm area of the coating region should be selected. On the SEM scan image, use image analysis software (e.g., ImageJ, NanoMeasurer, Matlab, etc.) to perform measurement and statistical processing to obtain the particle size of all first particles. Count the total number of primary particles in the first particles in this area as M. Among them, the number of individual primary particles with a particle size less than or equal to 0.3μm is N. Then, within the 100μm×100μm area of the coating surface, the proportion of the number of primary particles of the first particles with a particle size less than or equal to 0.3μm in the total number of primary particles in the first particles is (N / M)×100%. Repeat the above operation 5 times and take the average value as the final test result.
[0018] Research has shown that trace amounts of small-diameter first particles can undergo excessive swelling under the action of cyclic carbonates and can also be corroded by high content of fluoroethylene carbonate, causing the small-diameter first particles to dissolve and release trace amounts of first polymer or ester-containing groups. The first polymer and / or ester-containing groups can work together with fluoroethylene carbonate to form a more stable and flexible SEI film on the surface of the negative electrode, thereby reducing the risk of SEI film rupture during silicon material expansion, improving the cycle stability of the battery, improving the high-temperature adhesion between the separator and the electrode, reducing the high-temperature cycle impedance of the battery, and improving the high-temperature long-cycle performance of the battery.
[0019] To ensure that an appropriate amount of the first polymer and / or ester-containing groups can dissolve from the first particles, while synergistically cooperating with fluoroethylene carbonate to form a stable and flexible SEI, and to ensure the overall structural stability of the coating containing the first particles and avoid excessive dissolution of the first polymer, the battery of the present invention simultaneously controls the proportion of primary particles with a particle size of less than or equal to 0.3 μm in the primary particles of the first particles per unit area of the coating surface, as well as the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate.
[0020] Smaller-sized primary particles are more prone to excessive swelling under the influence of cyclic ethylene carbonate. By controlling the proportion of primary particles with a diameter of 0.3 μm or less within the above-mentioned range in the primary particles of the first particle per unit area of the coating surface, an appropriate amount of smaller-sized primary particles can be ensured in the coating. This facilitates the dissolution of an appropriate amount of the first polymer and / or ester-containing groups under the swelling effect of cyclic ethylene carbonate and the corrosion effect of fluoroethylene carbonate. This allows the first polymer and / or ester-containing groups to dissolve in synergistic effect with fluoroethylene carbonate to form a SEI film with high stability and good flexibility, thereby improving the cycle stability of the battery, reducing the high-temperature cycle impedance of the battery, and improving the high-temperature long-cycle performance of the battery. Moreover, controlling the proportion of primary particles with a diameter of 0.3 μm or less within the above-mentioned range in the primary particles of the first particle per unit area of the coating surface also ensures the presence of more larger-sized primary particles in the coating. Larger-sized primary particles are not easily swollen by cyclic carbonates or corroded by fluoroethylene carbonates, which can ensure the overall structural stability of the coating containing the first particles and avoid excessive dissolution of the first polymer and / or ester-containing groups. By controlling the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate within the aforementioned range, the cyclic ethylene carbonate and fluoroethylene carbonate can exert a synergistic effect. Under their combined action, trace amounts of small-diameter first particles can undergo excessive swelling under the action of cyclic ethylene carbonate. Simultaneously, the excessively swollen small-diameter first particles can cause trace amounts of the first polymer and / or ester-containing groups to dissolve from the first particles under the corrosion of fluoroethylene carbonate. This allows the first polymer and / or ester-containing groups to work together with fluoroethylene carbonate to form a more stable and flexible SEI film on the surface of the negative electrode. Simultaneously controlling the weight ratio of fluoroethylene carbonate in the electrolyte within the aforementioned range ensures an appropriate amount of fluoroethylene carbonate in the electrolyte. This avoids both excessive fluoroethylene carbonate, which would cause excessive corrosion of the first particle and affect the overall structural stability of the first particle, and insufficient fluoroethylene carbonate, which would prevent corrosion of the first particle, resulting in insufficient dissolution of the first polymer and / or ester-containing groups, thus hindering their synergistic effect with fluoroethylene carbonate to form a relatively stable and flexible SEI film on the surface of the negative electrode.
[0021] When the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate is less than 0.2:1, the excessive weight of fluoroethylene carbonate or the insufficient weight of cyclic ethylene carbonate in the electrolyte results in poor mechanical stability of the coating in the separator, leading to reduced structural mechanical strength of the separator coating and increased interfacial impedance between the separator and the electrode. This is detrimental to the separator's adhesion and high-temperature cycling performance at high temperatures. When the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate is greater than 1.5:1, the insufficient weight of fluoroethylene carbonate or the excessive weight of cyclic ethylene carbonate in the electrolyte results in excessive swelling of the first particles, reducing the lithium-ion permeability of the separator, increasing battery impedance, or preventing the dissolved first polymer and / or ester-containing groups from synergistically forming a stable and flexible SEI film on the negative electrode surface with sufficient fluoroethylene carbonate. This fails to effectively improve SEI film rupture, hindering the improvement of battery cycle stability and reduction of high-temperature cycle impedance.
[0022] It is understood that, in this invention, the corrosion of the first particle by fluoroethylene carbonate does not mean that the entire particle state of the first particle disappears or that the entire first particle is completely dissolved. Rather, it means that the particle state of a single first particle disappears completely or partially, or that some groups in a single first particle dissolve, or that the particle state of a single first particle is completely retained.
[0023] In this invention, the ester group dissolved from the first particle does not exist in the form of a functional group, but is a substance containing an ester group. This substance can be one or more of small molecules, monomers, oligomers, and ions.
[0024] In this invention, by simultaneously controlling the proportion of primary particles with a diameter of 0.3 μm or less in the first primary particles per unit area of the coating surface, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate, the high-temperature cycle impedance of the battery and the high-temperature long-cycle performance of the battery can be reduced compared with the prior art. To further improve the effect, one or more of the technical features can be further optimized.
[0025] In one example, within a 100μm × 100μm area on the surface of the coating, the number of primary particles of the first particle with a particle size less than or equal to 0.3μm accounts for 1%-3.5% of the total number of primary particles of the first particle.
[0026] In one example, the Dv95 of the first particle is 0.5μm-5μm (e.g., 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, or 5μm). In this invention, Dv95 is the particle size corresponding to 95% of the cumulative particle size distribution in the volumetric particle size distribution of the first particle. In this invention, the volumetric particle size distribution of the first particle can be obtained by arbitrarily selecting 100μm×100μm in the SEM image of the coating surface and combining it with image analysis software (e.g., ImageJ, NanoMeasurer, Matlab, etc.) for measurement and statistical processing to obtain Dv95. The Dv95 of the first particle can also be obtained by testing with a laser particle size analyzer, for example, before preparing the diaphragm, the Dv95 of the first particle can be obtained by measuring the first particle with a laser particle size analyzer.
[0027] In one instance, such as Figure 1 and Figure 2 As shown, the first particles are arranged in layers within the coating. The particles circled in red are the first particles, and only some of them are shown in the figure, not all of them. It can be understood that "layered arrangement" means that in the thickness direction of the membrane, the first particles are present in only one layer or multiple layers within the coating, and no large-size agglomerates appear.
[0028] In one example, the first particle constitutes 10%-100% of the mass of the coating (e.g., 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 100%).
[0029] In one example, the first polymer is an ester-containing and fluorine-free polymer.
[0030] In one example, the first polymer is an acrylate polymer.
[0031] In one example, the monomers forming the first polymer include one or more of methyl methacrylate, butyl acrylate, n-propyl acrylate, octyl acrylate, ethyl methacrylate, isooctyl acrylate, octadecyl acrylate, ethyl acrylate, cyclohexyl acrylate, and 2-hydroxyethyl acrylate.
[0032] In one example, the first polymer includes one or more of polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, acrylate-acrylonitrile copolymer (e.g., methyl methacrylate-acrylonitrile copolymer), acrylate-ethylene copolymer (e.g., methyl methacrylate-ethylene copolymer), acrylate-acrylonitrile-ethylene copolymer, styrene-acrylate monomer-acrylonitrile copolymer, ethylhexyl acrylate-methyl methacrylate copolymer, butyl acrylate-methyl methacrylate copolymer, methyl acrylate-N,N-dimethylacrylamide copolymer, ethyl acrylate-2-(diethylamino)ethyl acrylate copolymer, ethyl acrylate-N,N-diethylacrylamide copolymer, and ethyl acrylate-2-(diethylamino)ethyl acrylate.
[0033] In one example, the glass transition temperature of the first polymer is 40°C-75°C (e.g., 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, or 75°C).
[0034] In one example, the coating comprises ester groups.
[0035] In one example, the coating contains 20%-60% by weight of ester groups (e.g., 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%).
[0036] In one example, the coating further includes second particles, the composition of which includes a fluoropolymer. For example... Figure 1 and Figure 2 As shown, the second particle is an aggregated particle. The particles in the green circle are the second particles. It should be understood that only some of the second particles are shown in the figure, not all of them.
[0037] In one example, the monomers forming the fluoropolymer include one or more of vinylidene fluoride, tetrafluoroethylene, hexafluoroethylene, and hexafluoropropylene.
[0038] In one example, the fluoropolymer includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride, polyhexafluoropropylene, fluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.
[0039] In one example, the second particle constitutes 0%-90% of the coating by mass (e.g., 0, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 90%). When the second particle constitutes 0% of the coating by mass, it indicates that the second particle is absent from the coating.
[0040] In one example, the second particle includes secondary particles. In this invention, the secondary particles refer to aggregates formed by the aggregation of four or more primary particles.
[0041] In one example, the average particle size d1 of the secondary particles of the second particle is 2μm-15μm (e.g., 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm).
[0042] In one example, the average particle size d1 of the secondary particles of the second particle is 3 μm-10 μm.
[0043] In this invention, the average particle size of the secondary particles of the second particle can be obtained by the following method: On the scanned image of the sample coating surface obtained using SEM, draw the smallest square or rectangle that completely surrounds one secondary particle, that is, draw a square or rectangle whose edge of the secondary particle is connected to the four sides of the square or rectangle. The length of one side of the square or the length of the long side of the rectangle is the particle size of the secondary particle. In an arbitrary 10μm*10μm area on the coating surface, measure the particle size of any 100 secondary particles, and average the number of measurements as the average particle size. Repeat the above operation 5 times, and take the average value as the average particle size of the secondary particles. It should be noted that when 100 secondary particles can be observed in the captured image, the average particle size of any 100 secondary particles in the image is taken as the average particle size of the secondary particles. When no 100 secondary particles are observed in the image, take multiple images, and average the particle sizes of the total 100 secondary particles as the average particle size. The scanned images can be obtained by observing the surface of the coating using a scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.).
[0044] In one example, the battery satisfies the following relationship: 1 ≤ d1 / d2 ≤ 25 (e.g., 1, 3, 5, 8, 10, 13, 15, 18, 20, 23, or 25), where d1 is the average particle size of the secondary particles of the second particle, and d2 is the Dv95 of the first particle. Controlling the battery to satisfy the above relationship ensures that the coating, including the first and second particles, will not be excessively swollen at room temperature, thereby improving the mechanical stability of the coating at room temperature, enhancing the interfacial stability between the separator and the electrode at room temperature, reducing the room temperature cycle impedance of the battery, and improving the room temperature cycle performance of the battery.
[0045] In one instance, the battery satisfies the following relationship: 1.5 ≤ d1 / d2 ≤ 20.
[0046] According to one specific implementation, d1 is 2μm-15μm, d2 is 0.5μm-5μm, and the battery satisfies the following relationship: 1≤d1 / d2≤25.
[0047] According to one specific implementation, d1 is 3μm-10μm, d2 is 0.5μm-5μm, and the battery satisfies the following relationship: 1.5≤d1 / d2≤20.
[0048] In one example, the coating thickness is 0.5 μm to 5 μm (e.g., 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm).
[0049] In one example, based on the total weight of the coating, the first particles account for 10%-45% of the weight (e.g., 10%, 15%, 20%, 25%, 30%, 35%, 40%, or 45%), and the second particles account for 55%-90% of the weight (e.g., 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 90%).
[0050] In one example, the coating coverage on the carrier layer surface is 8%-100% (e.g., 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 100%). In this invention, the coating coverage on the carrier layer surface refers to the percentage of the orthographic projection area of the coating on one side of the carrier layer surface to the area of that side of the carrier layer (i.e., the surface of the carrier layer with the coating). When both sides of the carrier layer are coated, the coverage of the coating on both sides can be the same or different. The coating coverage on the carrier layer surface can be tested by the following method: obtaining a microscopic image of the coating surface using SEM, and randomly dividing the image into areas with a diameter of 100 μm. 2 The area (e.g., 100μm × 100μm) is divided into uniform 100*100 squares. If the area covered by the orthographic projection of the coating in a square exceeds half of the square's area, it means that the square is occupied by the coating; otherwise, it means that the square is not occupied by the coating. By counting the number of squares occupied by the coating, the total number of squares occupied by the coating is recorded as X. Then, the coverage rate = (X / 100*100)*100%. Repeat the above operation 5 times, and take the average of the 5 times as the coverage rate of the coating on the surface of the carrier layer.
[0051] In one example, the carrier layer includes a substrate layer and a heat-resistant layer located on one or both surfaces of the substrate layer.
[0052] In one example, the diaphragm includes a substrate layer, a heat-resistant layer, and a coating, wherein the heat-resistant layer is located on one side surface of the substrate layer and the coating is located on the other side surface of the substrate layer.
[0053] In one example, the diaphragm includes a substrate layer, a heat-resistant layer, and a coating, the heat-resistant layer being located on one side surface of the substrate layer, and the coating being located on the surface of the heat-resistant layer and the other side surface of the substrate layer.
[0054] In one example, the diaphragm includes a substrate layer, a heat-resistant layer, and a coating layer, the heat-resistant layer being located on both sides of the substrate layer, and the coating layer being located on the surface of the heat-resistant layer.
[0055] In one example, the heat-resistant layer comprises a third particle and a binder.
[0056] In one example, the third particle comprises boehmite, alumina, barium sulfate, magnesium oxide, magnesium hydroxide, silicon dioxide, tin dioxide, titanium dioxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, cerium oxide, zirconium titanate, barium titanate, magnesium fluoride, 1,3,5-triazine-2,4,6-triamine, melamine thiocyanate, melamine cyanurate, symmetrical triaminotriazine, and 2-(4-bromophenyl)-4,6-dimethyl-1 One or more of the following: 3,5-triazine, 1-(4,6-diamino-1,3,5-triazine-2-yl)guanidine, 2,4-diamino-6-dimethylamino-1,3,5-triazine, cyanuric chloride, 2,4,6-tris(2-pyridyl)triazine, 2,4,6-triphenyl-1,3,5-triazine, tris(tribromophenoxy)triazine, 2-amino-4,6-methoxy-1,3,5-triazine, uracil, cytosine, and lithium aluminum titanium phosphate.
[0057] In one example, the adhesive comprises one or more of the following: polyvinyl alcohol, styrene-butadiene rubber, ethylene-vinyl acetate copolymer, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, ethyl polyacrylate, polyacrylic acid, polyvinyl acetate, polyacrylate, polyurethane, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), and copolymer systems derived from the above polymers.
[0058] In one example, the weight ratio of the third particle to the adhesive is (30%-99%):(70%-1%) (e.g., 30%:70%, 40%:60%, 50%:50%, 60%:40%, 70%:30%, 80%:20%, 90%:10%, 91%:9%, 92%:8%, 93%:7%, 94%:6%, 95%:5%, 96%:4%, 97%:3%, 98%:2%, or 99%:1%). It is understood that the weight percentage of the third particle in the heat-resistant layer can be in the range of 30%-99%, and the weight percentage of the adhesive in the heat-resistant layer can be in the range of 70%-1%.
[0059] In one example, the adhesive is selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), and copolymer systems derived from the above polymers. The adhesive accounts for 30%-70% of the mass of the heat-resistant layer (e.g., 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%).
[0060] In one example, the adhesive is selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), and copolymer systems derived from the above polymers. The adhesive accounts for 35%-50% of the mass of the heat-resistant layer.
[0061] In one example, the adhesive is selected from one or more of polyvinyl alcohol, styrene-butadiene rubber, ethylene-vinyl acetate copolymer, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, ethyl polyacrylate, polyacrylic acid, polyvinyl acetate, polyacrylate, polyurethane, and copolymer systems derived from the above polymers. The adhesive accounts for 1%-10% of the heat-resistant layer by mass (e.g., 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%).
[0062] In one example, the heat-resistant layer further includes a thickener comprising one or more of methylcellulose (CMC), sodium carboxymethylcellulose (CMC-Na), and lithium carboxymethylcellulose (CMC-Li).
[0063] In one example, the weight percentage of the thickener in the heat-resistant layer is 0-1% (e.g., 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%). When the weight percentage of the thickener in the heat-resistant layer is 0, it indicates that there is no thickener in the heat-resistant layer.
[0064] In one example, the Dv10 of the third particle is 0.01 μm-1.5 μm (e.g., 0.01 μm, 0.05 μm, 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.3 μm, or 1.5 μm). Controlling the Dv10 of the third particle within the above range can improve the adhesion strength between the heat-resistant layer and the coating, while also improving the flexibility of the heat-resistant layer, improving the adhesion between the separator and the electrode, improving the lithium-ion transport rate, and improving the room-temperature cycle performance of the battery.
[0065] In this invention, Dv10 refers to the particle size corresponding to a cumulative particle size distribution of 10% in the volumetric particle size distribution of the third particle. The Dv10 of the third particle can be obtained by testing with a laser particle size analyzer.
[0066] In one example, the thickness of the heat-resistant layer is 0.2 μm to 5 μm (e.g., 0.2 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm).
[0067] In one example, the thickness of the substrate layer is 2μm-10μm (e.g., 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm).
[0068] In one example, the porosity of the substrate layer is 25%-70% (e.g., 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%).
[0069] In one example, the substrate layer comprises one or more of the following polymer derivatives: polyolefin (e.g., PP, PE), polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl chloride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyethylene terephthalate, polybutylene terephthalate, poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), and poly(m-phenylene isophthalamide).
[0070] In one example, after the diaphragm is compressed at 2 MPa for 0.5 h at 80°C, the compression rate of the diaphragm is 10%-50% (e.g., 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%).
[0071] In this invention, the compressibility of the separator can be obtained by testing it using the following method: The compressibility of the separator is a well-known concept in the art and can be tested using well-known equipment and methods, such as testing according to the national standard GB / T1041-2008 Test for Compression Performance of Plastics. Specifically, the separator may originate from the separator itself or from the battery cell. When the separator originates from the separator itself, drying treatment is not required, and the compression performance can be tested directly. When the separator originates from the battery cell, drying treatment is required before testing the compression performance. The drying process is as follows: Disassemble the battery cell, remove the separator, and place the separator in an oven at 60°C for 2 hours. The compression performance testing process is as follows: Lay the separator flat on a flat aluminum foil surface and cover it with another layer of aluminum foil to ensure the separator is flat. Fifty samples (e.g., 5cm × 5cm) of diaphragm with a fixed area were cut. Each sample had aluminum foil covering both its top and bottom surfaces. These 50 samples were stacked together for subsequent compression testing. One hundred pieces of aluminum foil of the same size were also cut and stacked together as a blank group. A universal tensile testing machine was used in compression mode at a speed of 0.5 mm / min. The stress-strain curves were recorded to obtain the compression ratio of the diaphragm samples.
[0072] According to a specific embodiment, within a 100μm × 100μm area on the surface of the coating, the number of primary particles with a particle size less than or equal to 0.3μm accounts for 0.01%-4% of the total number of primary particles; the Dv95 of the first particles is 0.5μm-5μm; the first particles are arranged in a stacked manner in the coating; the average particle size d1 of the secondary particles of the second particles is 3μm-10μm; the battery satisfies the following relationship: 1.5≤d1 / d2≤20; the thickness of the coating is 0.5μm-5μm; the weight percentage of ester groups in the coating is 20%-60%; the first polymer includes polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, acrylate-acrylonitrile copolymer, acrylate-acrylonitrile-ethylene copolymer, and styrene-acrylate. The diaphragm comprises one or more of the following: a copolymer of monomer-acrylonitrile, a copolymer of ethylhexyl acrylate-methyl methacrylate, a copolymer of butyl acrylate-methyl methacrylate, a copolymer of methyl acrylate-N,N-dimethylacrylamide, a copolymer of ethyl acrylate-2-(diethylamino)ethyl acrylate, a copolymer of ethyl acrylate-N,N-diethylacrylamide, and ethyl acrylate-2-(diethylamino)ethyl acrylate; the fluoropolymer comprises one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride, polyhexafluoropropylene, fluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer; the diaphragm satisfying the above characteristics can achieve a compression ratio of 10%-50% after being compressed at 80°C and under a pressure of 2MPa for 0.5h.
[0073] In one example, after the membrane is baked at 80°C for 2 hours, the porosity of the membrane is 30%-60% (e.g., 30%, 33%, 35%, 38%, 40%, 43%, 45%, 48%, 50%, 53%, 55%, 58%, or 60%).
[0074] In this invention, the porosity of the diaphragm can be obtained by the following method: the diaphragm is kneaded into a ball and inserted into a 3.5 mL sample cup. The sample cup containing the sample is placed in a true density analyzer, the testing system is sealed, and helium gas is introduced according to the program. By detecting the gas pressure in the sample chamber and the expansion chamber, and then calculating the true volume according to Bohr's Law (PV = nRT), the porosity of the sample to be tested is obtained. Porosity = (V1 - V2) / V1 * 100%, where V1 is the apparent volume of the sample, and V2 is the true volume of the sample.
[0075] According to a specific embodiment, within a 100μm × 100μm area on the surface of the coating, the number of primary particles with a particle size less than or equal to 0.3μm accounts for 0.01%-4% of the total number of primary particles; the Dv95 of the first particles is 0.5μm-5μm; the first particles are arranged in a stacked manner in the coating; the average particle size d1 of the secondary particles of the second particles is 3μm-10μm; the battery satisfies the following relationship: 1.5≤d1 / d2≤20; the thickness of the coating is 0.5μm-5μm; the weight percentage of ester groups in the coating is 20%-60%; the first polymer includes polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, acrylate-acrylonitrile copolymer, acrylate-acrylonitrile-ethylene copolymer, styrene-ethylhexyl acrylate, etc. The membrane comprises one or more of the following: copolymers of olefin-acrylate monomers-acrylonitrile, copolymers of ethylhexyl acrylate-methyl methacrylate, copolymers of butyl acrylate-methyl methacrylate, copolymers of methyl acrylate-N,N-dimethylacrylamide, copolymers of ethyl acrylate-2-(diethylamino)ethyl acrylate, copolymers of ethyl acrylate-N,N-diethylacrylamide, and ethyl acrylate-2-(diethylamino)ethyl acrylate; the fluoropolymer comprises one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride, polyhexafluoropropylene, fluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer; the membrane satisfying the above characteristics has a porosity of 30%-60% after baking at 80°C for 2 hours.
[0076] According to a specific embodiment, within a 100μm × 100μm area on the surface of the coating, the number of primary particles with a particle size less than or equal to 0.3μm accounts for 0.01%-4% of the total number of primary particles; the Dv95 of the first particles is 0.5μm-5μm; the first particles are arranged in a stacked manner in the coating; the average particle size d1 of the secondary particles of the second particles is 3μm-10μm; the battery satisfies the following relationship: 1.5≤d1 / d2≤20; the thickness of the coating is 0.5μm-5μm; the weight percentage of ester groups in the coating is 20%-60%; the first polymer includes polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, acrylate-acrylonitrile copolymer, acrylate-acrylonitrile-ethylene copolymer, styrene-acrylate monomer-acrylonitrile copolymer, acrylic acid The diaphragm comprises one or more of the following: ethylhexyl acrylate-methyl methacrylate copolymer, butyl acrylate-methyl methacrylate copolymer, methyl acrylate-N,N-dimethylacrylamide copolymer, ethyl acrylate-2-(diethylamino)ethyl acrylate copolymer, ethyl acrylate-N,N-diethylacrylamide copolymer, and ethyl acrylate-2-(diethylamino)ethyl acrylate; the fluoropolymer comprises one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride, polyhexafluoropropylene, fluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer; the diaphragm satisfying the above characteristics can achieve a compression ratio of 10%-50% after being compressed at 80°C under a pressure of 2MPa for 0.5h, and a porosity of 30%-60% after being baked at 80°C for 2h.
[0077] In one example, the electrolyte contains fluoroethylene carbonate at a weight percentage of 13%-50% (13%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%).
[0078] In one example, the electrolyte contains 15%-35% fluoroethylene carbonate by weight.
[0079] In one example, the cyclic carbonate includes ethylene carbonate and / or propylene carbonate.
[0080] In one example, the cyclic carbonate in the electrolyte accounts for 5% to 50% by weight (e.g., 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%).
[0081] In one example, the cyclic carbonate in the electrolyte accounts for 10%-25% by weight.
[0082] In one example, the weight ratio of the cyclic ethylene carbonate to the fluoroethylene carbonate is (0.6-1.1):1.
[0083] According to one specific embodiment, the weight percentage of fluoroethylene carbonate in the electrolyte is 13%-50%, the weight percentage of cyclic carbonate in the electrolyte is 5%-50%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate is (0.2-1.5):1.
[0084] According to one specific embodiment, the weight percentage of fluoroethylene carbonate in the electrolyte is 15%-35%, the weight percentage of cyclic carbonate in the electrolyte is 10%-25%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate is (0.6-1.1):1.
[0085] In one example, the electrolyte includes a lithium salt, an organic solvent, and additives.
[0086] In one example, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium tetrafluoroborate, lithium di(oxalate)borate, lithium di(fluorooxalate)borate, and lithium di(fluorobis(oxalate))phosphate.
[0087] In one example, the organic solvent includes one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl formate (MF), methyl acetate (MA), methyl butyrate (MB), ethyl propionate (EP), propyl propionate (PP), ethyl butyrate, propyl acetate, and ethyl difluoroacetate.
[0088] In one example, the additives include film-forming additives for the negative electrode surface, film-forming additives for the positive electrode surface, and film-forming additives for the positive and negative electrode current collector surfaces; they may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc. The additives may be one or more of the following: dinitrile compounds, trinitrile compounds, fluorinated chain carbonates, fluorinated carboxylic acid esters, and sulfur-containing compounds.
[0089] Dinitrile compounds include, but are not limited to: succinic anion, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanoctane, 1,9-dicyanonane, 1,10-dicyanodecane, 1,12-dicyanodedecane, tetramethylsuccinic anion, 2-methylglutaronitrile, 2,4-dimethylpentane, 2,2,4,4-tetramethylglutaronitrile Nitriles, 1,5-dicyanopentane, 2,6-dicyanopentane, 2,7-dicyanopentane, 2,8-dicyanopentane, 1,6-dicyanopentane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-heptanenitrile, 1,4-di(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether, diethylene glycol di(2-cyanoethyl) ether, tri... Ethylene glycol di(2-cyanoethyl) ether, tetraethylene glycol di(2-cyanoethyl) ether, 3,6,9,12,15,18-hexaoxaneicosanoic acid dionitrile, 1,3-di(2-cyanoethoxy)propane, 1,4-di(2-cyanoethoxy)butane, 1,5-di(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl) ether, 1,4-dicyano-2-butene, 1,4 One or more of the following: cyano-2-methyl-2-butene, 1,4-cyano-2-ethyl-2-butene, 1,4-cyano-2,3-dimethyl-2-butene, 1,4-cyano-2,3-diethyl-2-butene, 1,6-cyano-3-hexene, 1,6-cyano-2-methyl-3-hexene, or 1,6-cyano-2-methyl-5-methyl-3-hexene.
[0090] Trinitrile compounds include, but are not limited to, one or more of the following: 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane, or 1,2,5-tris(cyanoethoxy)pentane.
[0091] Sulfur-containing compounds include, but are not limited to, one or more of the following: 1,3-propanesulfonate lactone, vinyl sulfate, cyclic sulfate, chain sulfate, chain sulfonate, cyclic sulfonate, chain sulfite, cyclic sulfite, chain sulfone, and cyclic sulfone.
[0092] Fluorinated chain carbonates include, but are not limited to, one or more of the following: fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate, or bis(trifluoroethyl) carbonate.
[0093] In one example, based on the total weight of the electrolyte, the lithium salt accounts for 5%-30% by weight (e.g., 5%, 10%, 15%, 20%, 25%, or 30%), the organic solvent accounts for 0%-60% by weight (e.g., 0, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%), and the additive accounts for 0%-30% by weight (e.g., 0, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, or 30%). When the weight percentage of the organic solvent in the electrolyte is 0, it indicates that there is no organic solvent in the electrolyte. When the weight percentage of the additive in the electrolyte is 0, it indicates that there is no additive in the electrolyte.
[0094] In one example, the negative electrode includes a negative current collector and a negative active layer located on one or both surfaces of the negative current collector, with the coating corresponding to the negative active layer. It is understood that when the coating is located on one surface of the carrier layer, the negative electrode corresponds to the coated side of the separator, and the positive electrode corresponds to the other side of the separator; when the coating is located on both surfaces of the carrier layer, the negative electrode corresponds to either coated side of the separator, and the positive electrode corresponds to the other side of the separator.
[0095] In one example, the membrane includes a carrier layer and coatings located on both sides of the carrier layer. The coating corresponding to the negative electrode active layer is composed of first particles, and the coating corresponding to the positive electrode active layer is composed of first particles and second particles.
[0096] In one example, the negative electrode active layer comprises a silicon-based material, which includes one or more of elemental silicon particles, silicon oxide particles, silicon-carbon composite particles, silicon-nitrogen composite particles, and silicon alloy particles.
[0097] In one example, the average particle size of the silicon-carbon composite particles is 5 μm-12 μm (e.g., 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm).
[0098] In this invention, the average particle size of the silicon-carbon composite particles can be obtained by the following method: On a scanned image of the surface of the negative electrode active layer obtained using SEM, draw a square or rectangle with the smallest area that completely surrounds one silicon-carbon composite particle. That is, draw a square or rectangle where the edge of the silicon-carbon composite particle is connected to the four sides of the square or rectangle. The length of one side of the square or the length of the long side of the rectangle is the particle size of the silicon-carbon composite particle. In an area of arbitrarily selected 10μm*10μm on the surface of the negative electrode active layer, measure the particle size of any 100 silicon-carbon composite particles, and average the number of measurements as the average particle size. Repeat the above operation 5 times, and take the average value as the average particle size of the silicon-carbon composite particles. It should be noted that when 100 silicon-carbon composite particles can be observed in the captured image, the average particle size of any 100 silicon-carbon composite particles in the image is taken as the average particle size of the silicon-carbon composite particles. When no 100 silicon-carbon composite particles are observed in the image, take multiple images, and average the total number of particle sizes of 100 silicon-carbon composite particles as the average particle size. The scanned images can be obtained by observing the surface of the coating using a scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.).
[0099] In one example, the graphitization degree of the silicon-carbon composite particles is 0-0.85 (e.g., 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.85). Controlling the graphitization degree of the silicon-carbon composite particles within the above range can balance the electron migration resistance of the silicon-carbon composite particles and the stability of the SEI film. While a high graphitization degree results in high mechanical strength and low electron migration resistance for the silicon-carbon composite particles, it also leads to lower toughness and less ability to absorb volumetric strain of silicon.
[0100] In this invention, the degree of graphitization of the silicon-carbon composite particles can be obtained by testing using the following method: X-ray diffraction (XRD), for example, using a Shimadzu XRD-6100 X-ray diffractometer, with a sample volume of 0.5 g / cm³. 2 The Kα line of Cu was used as the incident X-ray. The working voltage of the X-ray source was 40 kV and the test power was 2 kW. 2θ was used as the abscissa and the unit was °. The signal intensity was used as the ordinate. The test range was 10 to 80°. The scanning rate was 4° / min and the data point interval was 0.02°. Based on the position of the (002) peak of the material in the range of 2θ = 22.5°-26.5°, the interlayer spacing d002 of the (002) peak was calculated by Bragg formula. Then, the graphitization degree g value was calculated by Mering–Maire formula g = (0.3440-d002) / (0.3440-0.3354).
[0101] In one example, the sphericity of the silicon-carbon composite particles is 0.6-1 (e.g., 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 1).
[0102] In this invention, the sphericity of the silicon-carbon composite particles can be tested by the following method: taking an image of the particles on the surface of the negative electrode active layer by scanning electron microscopy (SEM), using image processing software to draw the smallest rectangle that completely surrounds one particle on the obtained scan image, that is, drawing the rectangle whose edge of the silicon-carbon composite particle is connected to the four sides of the rectangle, measuring the longest side and the shortest side of the rectangle, and calculating the sphericity = shortest side / longest side.
[0103] In one example, the negative electrode active layer includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder, wherein the negative electrode active material includes silicon-based materials and carbon-based materials. The negative electrode active layer includes silicon.
[0104] In one example, the carbon-based material includes graphite.
[0105] In one example, the weight content of the negative electrode active material is 95%-98.5% (e.g., 95%, 96%, 97%, 98%, or 98.5%), based on the total weight of the negative electrode active material layer.
[0106] In one example, the weight content of silicon element is 3%-70% (e.g., 3%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%), based on the total weight of the negative electrode active material layer.
[0107] In one example, the silicon content is 7%-30% by weight, based on the total weight of the negative electrode active material layer.
[0108] In one example, the negative electrode active material layer further includes a negative electrode conductive agent and a negative electrode binder.
[0109] In one example, the negative electrode conductive agent includes one or more of furnace black, acetylene black, Ketjen black, and carbon nanotubes.
[0110] In one example, the negative electrode binder includes one or more of acrylic acid-acrylonitrile copolymer, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylic acid (PAA), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR).
[0111] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode conductive agent is 0.1%-1.5% (e.g., 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, or 1.5%), and the weight content of the negative electrode binder is 0.5%-3.5% (e.g., 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or 3.5%).
[0112] In one example, the battery includes a positive electrode. The positive electrode can be a conventional positive electrode, for example, the positive electrode includes a positive current collector and a positive active layer located on at least one surface of the positive current collector. The positive active layer can have a conventional composition in the art.
[0113] In one example, the battery is a lithium-ion rechargeable battery.
[0114] The present invention will be described in detail below through embodiments. The embodiments described herein are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0115] The following examples illustrate the battery of the present invention.
[0116] Example 1
[0117] (1) Diaphragm
[0118] The third particle (alumina) and polyacrylic acid (binder) are mixed and stirred thoroughly to obtain a mixed slurry with a solid content of 25%. The slurry has a 100% solid mass ratio of alumina to polyacrylic acid (by weight) of 96% to 4%. The mixed slurry is coated onto one side of the base material (PE) using a gravure roller. After drying in a multi-section oven at 60°C, a heat-resistant layer is formed with a thickness of 1 μm.
[0119] The first particle (methyl methacrylate-acrylonitrile copolymer) and the second particle (PVDF-HFP copolymer) are dispersed in deionized water (wherein, the first particle accounts for 40% of the mass of the coating and the second particle accounts for 60% of the mass of the coating). After thorough stirring, a first slurry with a solid content of 10% is obtained. The first particle (methyl methacrylate-acrylonitrile copolymer) is dispersed in deionized water and stirred thoroughly to obtain a second slurry with a solid content of 10%. The first slurry is coated on the surface of the heat-resistant layer using a gravure roller, and the second slurry is coated on the other side of the substrate layer. After drying in a multi-section oven at 60°C, a coating is formed.
[0120] Specifically, within a 100μm×100μm area on the surface of the coating, the number of primary particles with a particle size less than or equal to 0.3μm accounts for 1.4% of the total number of primary particles in the first particle, the Dv95 of the first particle is 0.9μm, the average particle size d1 of the secondary particles in the second particle is 6.2μm, d1 / d2=6.2 / 0.9=6.89, and the coverage of the coating on the surface of the carrier layer is 20%.
[0121] (2) Electrolyte
[0122] In an argon-filled glove box (moisture <1 ppm, oxygen <1 ppm), ethylene carbonate, propylene carbonate, propyl propionate, and ethyl propionate solvents were mixed to form a homogeneous solvent. LiPF6, 1,3,6-hexanetrionitrile, and fluoroethylene carbonate were then slowly added. After thorough stirring, an electrolyte was obtained, in which LiPF6 accounted for 16% by weight, 1,3,6-hexanetrionitrile accounted for 3% by weight, fluoroethylene carbonate accounted for 21.1% by weight, cyclic ethylene carbonate accounted for 18.4% by weight (the weight ratio of ethylene carbonate to propylene carbonate was 0.5:1), and the weight ratio of propyl propionate to ethyl propionate was 5:2.
[0123] (3) Negative electrode sheet
[0124] Carbon-based material (graphite), silicon-based material (silicon-carbon composite particles with an average particle size of 8 μm, graphitization degree of 0.1, and sphericity of 0.8), negative electrode conductive agent (carbon black:carbon nanotubes (weight ratio) = 1:1), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber) were mixed in an aqueous solvent at a weight ratio of 86:12:1:0.5:0.5 and continuously stirred under the action of a stirrer to form a homogeneous and fluid negative electrode slurry. Subsequently, the slurry was coated on both sides of a 10 μm thick current collector copper foil to form a negative electrode active layer, and then dried in a vacuum oven at 120℃ for 6 hours. After rolling and slitting, the negative electrode sheet was obtained.
[0125] (4) Positive electrode plate
[0126] Lithium cobalt oxide, polyvinylidene fluoride (PVDF 500) binder, and conductive material (Super P: carbon nanotubes = 2:1) were mixed in N-methylpyrrolidone (NMP) solvent at a weight ratio of 98:2:2 and continuously stirred under the action of a stirrer to form a homogeneous and fluid positive electrode slurry. Subsequently, the positive electrode slurry was coated onto an aluminum foil with a thickness of 10 μm and dried in a vacuum oven at 120 °C for 6 hours. Then, it was rolled and slit to obtain the desired positive electrode sheet.
[0127] (5) Lithium-ion batteries
[0128] The positive electrode sheet obtained in step (4), the separator obtained in step (1), and the negative electrode sheet obtained in step (34) are wound together to form a bare battery cell. Then, the bare battery cell is placed in an aluminum-plastic film, and the electrolyte obtained in step (2) is injected into the dried bare battery cell. After vacuum sealing, room temperature standing, high temperature formation and other processes, the desired lithium-ion battery is obtained.
[0129] Example 2 group
[0130] This set of embodiments is used to illustrate the effect when the proportion of the number of primary particles of the first particle with a particle size less than or equal to 0.3 μm in the primary particles of the first particle changes within a 100 μm × 100 μm area on the surface of the coating.
[0131] Example 2a
[0132] The same procedure was followed as in Example 1, except that the number of primary particles of the first particle with a particle size less than or equal to 0.3 μm in the 100 μm × 100 μm area of the surface of the coating was 0.016%.
[0133] Example 2b
[0134] The same procedure was carried out as in Example 1, except that, within a 100μm × 100μm area on the surface of the coating, the number of primary particles of the first particle with a particle size less than or equal to 0.3μm accounted for 0.57% of the total number of primary particles of the first particle.
[0135] Example 2c
[0136] The same procedure was carried out as in Example 1, except that, within a 100μm × 100μm area on the surface of the coating, the number of primary particles of the first particle with a particle size less than or equal to 0.3μm accounted for 2.33% of the total number of primary particles of the first particle.
[0137] Example 2d
[0138] The same procedure was followed as in Example 1, except that, within a 100μm × 100μm area on the surface of the coating, the number of primary particles of the first particle with a particle size less than or equal to 0.3μm accounted for 3.96% of the total number of primary particles of the first particle.
[0139] Example 3 Group
[0140] This set of examples illustrates the effects of changes in the weight percentage of fluoroethylene carbonate in the electrolyte.
[0141] Example 3a
[0142] The experiment was conducted in accordance with Example 1, except that the weight percentage of fluoroethylene carbonate in the electrolyte was 13%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 1.42.
[0143] Example 3b
[0144] The experiment was conducted in accordance with Example 1, except that the weight percentage of fluoroethylene carbonate in the electrolyte was 15%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 1.23.
[0145] Example 3c
[0146] The experiment was conducted in accordance with Example 1, except that the weight percentage of fluoroethylene carbonate in the electrolyte was 35%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 0.53.
[0147] Example 3d
[0148] The experiment was conducted in accordance with Example 1, except that the weight percentage of fluoroethylene carbonate in the electrolyte was 50%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 0.37.
[0149] Example 4 group
[0150] This set of examples illustrates the effects of changing the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate.
[0151] Example 4a
[0152] The experiment was conducted in accordance with Example 1, except that the weight percentage of fluoroethylene carbonate in the electrolyte was 24.5%, the weight percentage of cyclic ethylene carbonate in the electrolyte was 5%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 0.2.
[0153] Example 4b
[0154] The experiment was conducted in accordance with Example 1, except that the weight percentage of cyclic ethylene carbonate in the electrolyte was 10%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 0.47.
[0155] Example 4c
[0156] The experiment was conducted in accordance with Example 1, except that the weight percentage of cyclic ethylene carbonate in the electrolyte was 25%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 1.18.
[0157] Example 4d
[0158] The experiment was conducted in accordance with Example 1, except that the electrolyte contained 33.6% fluoroethylene carbonate by weight, 50% cyclic ethylene carbonate by weight, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 1.49. The electrolyte contained 15% LiPF6 by weight, 1.4% 1,3,6-hexanetrionitrile by weight, and propyl propionate and ethyl propionate were not present in the electrolyte.
[0159] Example 5 group
[0160] This set of examples illustrates the effects that occur when d1 / d2 changes.
[0161] Example 5a
[0162] The same procedure was performed as in Example 1, except that d1 was 9.7 μm, d2 was 0.5 μm, and d1 / d2 = 9.7 / 0.5 = 19.4.
[0163] Example 5b
[0164] The same procedure was performed as in Example 1, except that d1 was 5.2 μm, d2 was 4.9 μm, and d1 / d2 = 5.2 / 4.9 = 1.06.
[0165] Example 5c
[0166] The same procedure was performed as in Example 1, except that d1 was 14.8 μm, d2 was 0.6 μm, and d1 / d2 = 14.8 / 0.6 = 24.67.
[0167] Example 5d
[0168] The same procedure was performed as in Example 1, except that d1 was 3.1 μm, d2 was 2 μm, and d1 / d2 = 3.1 / 2 = 1.55.
[0169] Example 5e
[0170] The same procedure was performed as in Example 1, except that d1 was 2.3 μm, d2 was 1.3 μm, and d1 / d2 = 2.3 / 1.3 = 1.77.
[0171] Example 5f
[0172] The same procedure was performed as in Example 1, except that d1 was 2.3 μm, d2 was 2.7 μm, and d1 / d2 = 2.3 / 2.7 = 0.85.
[0173] Example 5g
[0174] The same procedure was performed as in Example 1, except that d1 was 14.8 μm, d2 was 0.5 μm, and d1 / d2 = 14.8 / 0.5 = 29.6.
[0175] Example 5h
[0176] The same procedure was performed as in Example 1, except that d1 was 16.6 μm, d2 was 5.3 μm, and d1 / d2 = 16.6 / 5.3 = 3.13.
[0177] Example 5i
[0178] The same procedure was performed as in Example 1, except that d1 was 1.8 μm, d2 was 0.4 μm, and d1 / d2 = 1.8 / 0.4 = 4.5.
[0179] Example 6 group
[0180] This set of examples illustrates the effects that occur when the composition of the first particle changes.
[0181] Example 6a
[0182] The procedure was carried out in accordance with Example 1, except that the first particle was composed of methacrylate-ethylene copolymer.
[0183] Example 6b
[0184] The procedure was carried out in accordance with Example 1, except that the first particle was composed of an acrylate-acrylonitrile-ethylene copolymer.
[0185] Example 7 group
[0186] This set of examples illustrates the effects that occur when the composition of the second particle changes.
[0187] Example 7a
[0188] The procedure was carried out in accordance with Example 1, except that the second particle was composed of PVDF.
[0189] Example 7b
[0190] The procedure was carried out in accordance with Example 1, except that the second particle was composed of vinyl chloride-hexafluoroolefin copolymer.
[0191] Example 8 group
[0192] This set of examples illustrates the effects of changing the specific choice of cyclic ethylene carbonate.
[0193] Example 8a
[0194] The procedure was carried out in accordance with Example 1, except that all cyclic ethylene carbonates were EC.
[0195] Example 8b
[0196] The procedure was carried out in accordance with Example 1, except that all cyclic ethylene carbonates were PC.
[0197] Example 9 group
[0198] Example 9a
[0199] The same procedure was performed as in Example 1, except that the coating coverage on the carrier layer surface was 8%, the average particle size of the silicon-carbon composite particles was 5.1 μm, the degree of graphitization of the silicon-carbon composite particles was 0.82, and the sphericity of the silicon-carbon composite particles was 0.95.
[0200] Example 9b
[0201] The process was carried out in accordance with Example 1, except that the coating coverage on the carrier layer surface was 70%, the average particle size of the silicon-carbon composite particles was 11.7 μm, the degree of graphitization of the silicon-carbon composite particles was 0.46, and the sphericity of the silicon-carbon composite particles was 0.62.
[0202] Example 9c
[0203] The procedure was carried out in accordance with Example 1, except that the silicon-based material was silicon oxide particles with an average particle size of 9 μm.
[0204] Example 10 group
[0205] This set of examples illustrates the effects that occur when the composition of the third particle changes.
[0206] Example 10a
[0207] The procedure was carried out in accordance with Example 1, except that the third particle was composed of uracil.
[0208] Example 10b
[0209] The procedure was carried out in accordance with Example 1, except that the third particle was composed of cytosine.
[0210] Example 10c
[0211] The procedure was carried out in accordance with Example 1, except that the third particle was composed of melamine cyanurate.
[0212] Example 11
[0213] The process is carried out in accordance with Example 1, except that a second slurry is not used, and the first slurry is coated on the surface of the heat-resistant layer and the other side of the substrate layer, that is, the coating on the surface of the heat-resistant layer is the same as the coating on the other side of the substrate layer.
[0214] Comparative Example 1
[0215] The same procedure was followed as in Example 1, except that the number of primary particles of the first particle with a particle size less than or equal to 0.3 μm in the 100 μm × 100 μm area of the coating surface was 0.
[0216] Comparative Example 2
[0217] The same procedure was followed as in Example 1, except that the number of primary particles of the first particle with a particle size less than or equal to 0.3 μm in the 100 μm × 100 μm area of the coating surface accounted for 4.2% of the total number of primary particles of the first particle.
[0218] Comparative Example 3
[0219] The experiment was conducted in accordance with Example 1, except that the weight percentage of fluoroethylene carbonate in the electrolyte was 12.5%, the weight percentage of cyclic ethylene carbonate in the electrolyte was 5%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 0.4.
[0220] Comparative Example 4
[0221] The experiment was conducted in accordance with Example 1, except that the weight percentage of fluoroethylene carbonate in the electrolyte was 51%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 0.36.
[0222] Comparative Example 5
[0223] The experiment was conducted in accordance with Example 1, except that the weight percentage of fluoroethylene carbonate in the electrolyte was 33.6%, the weight percentage of cyclic ethylene carbonate in the electrolyte was 6.2%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 0.18.
[0224] Comparative Example 6
[0225] The experiment was conducted in accordance with Example 1, except that the weight percentage of fluoroethylene carbonate in the electrolyte was 31.2%, the weight percentage of cyclic ethylene carbonate in the electrolyte was 50%, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate was 1.6.
[0226] Comparative Example 7
[0227] The same procedure was followed as in Example 1, except that the first particle was not present in the coating.
[0228] Test case
[0229] The lithium-ion batteries prepared by the examples and comparative examples were subjected to the following tests:
[0230] 1. High-temperature (60℃) cyclic impedance change rate test
[0231] The lithium-ion battery was transferred to a 60°C environment and allowed to stand for 30 minutes. It was then discharged at a constant current of 0.2C to 3.0V, allowed to stand for 5 minutes, charged at 0.5C to 4.53V, and then charged at a constant voltage to the cutoff current of 0.05C. After standing for 5 minutes, the initial fully charged impedance value R1 was measured using an electrochemical workstation. The battery was then discharged at a constant current of 0.7C to 3.0V. This cycle was repeated for 30 cycles: charging at 0.5C to 4.53V, charging at a constant voltage to the cutoff current of 0.05C, allowing to stand for 5 minutes, and then discharging at a constant current of 0.7C to 3.0V. After the cycle, the battery was charged at 0.5C to 4.53V, charged at a constant voltage to the cutoff current of 0.05C, allowed to stand for 5 minutes, and the fully charged impedance value R2 after the cycle was measured using an electrochemical workstation. The impedance change rate was calculated as: [(R2-R1) / R1]×100%.
[0232] 2. Room temperature long-cycle impedance change rate test
[0233] Transfer the lithium-ion battery to a 25°C environment and let it stand for 30 minutes. Discharge it at a constant current of 0.2C to 3.0V, let it stand for 5 minutes, then charge it at 0.5C to 4.53V. Then charge it at a constant voltage to the cutoff current of 0.05C, let it stand for 5 minutes, and use an electrochemical workstation to measure the initial fully charged impedance value R1. Then discharge it at a constant current of 0.7C to 3.0V. Cycle it 1000 times using the following steps: charge at 0.5C to 4.53V, then charge at a constant voltage to the cutoff current of 0.05C, let it stand for 5 minutes, and discharge at a constant current of 0.7C to 3.0V. After cycling, charge it at 0.5C to 4.53V, then charge it at a constant voltage to the cutoff current of 0.05C, let it stand for 5 minutes, and use an electrochemical workstation to measure the fully charged impedance value R2 after cycling. The impedance change rate is calculated as: [(R2-R1) / R1]×100%.
[0234] 3. Room temperature long-cycle capacity retention test:
[0235] At 25℃±2℃, the battery was charged at 0.7C constant current and constant voltage to the upper limit voltage of 4.53V, cut off at 0.05C, and the initial thickness P0 was recorded. Then, it was discharged at 0.2C constant current to the lower limit voltage of 3.0V, and the initial discharge capacity was recorded as C0. After resting for 10 minutes, the cycle was repeated as follows: 3C constant current and constant voltage charging to 4.25V, cut off at 2C, then 2C constant current and constant voltage charging to 4.48V, cut off at 1.5C, then 1.5C constant current and constant voltage charging to the upper limit voltage of 4.53V, cut off at 0.18C, rested for 5 minutes, and then discharged at 0.7C to the lower limit voltage of 3.0V. After 1000 cycles, the battery was charged at 0.7C constant current and constant voltage to the upper limit voltage of 4.53V, cut off at 0.05C, and the final thickness P1 was recorded. Then, it was discharged at 0.2C constant current to the lower limit voltage of 4.53V, and the final discharge capacity was recorded as C1. Capacity retention rate: C = C1 / C0 * 100%.
[0236] 4. High-temperature cycling capacity retention test:
[0237] At 45℃, the battery was charged at 0.7C constant current and constant voltage to the upper limit voltage of 4.53V, cut off at 0.05C, and the initial thickness P0 was recorded. Then, it was discharged at 0.2C constant current to the lower limit voltage of 3.0V, and the initial discharge capacity was recorded as C0. After resting for 10 minutes, the cycle was repeated as follows: 3C constant current and constant voltage charging to 4.25V, cut off at 2C, then 2C constant current and constant voltage charging to 4.48V, cut off at 1.5C, then 1.5C constant current and constant voltage charging to the upper limit voltage of 4.53V, cut off at 0.18C, rested for 5 minutes, and then discharged at 0.7C to the lower limit voltage of 3.0V. After 300 cycles, the battery was charged at 0.7C constant current and constant voltage to the upper limit voltage of 4.53V, cut off at 0.05C, and the final thickness P1 was recorded. Then, it was discharged at 0.2C constant current to the lower limit voltage of 4.53V, and the final discharge capacity was recorded as C1. Capacity retention rate: C = C1 / C0 * 100%.
[0238] The results are recorded in Table 1.
[0239] Table 1
[0240]
[0241]
[0242] As can be seen from Table 1, by comparing the comparative example and the embodiment, the high-temperature impedance change rate of the battery in the embodiment is significantly reduced, and the high-temperature cycle capacity retention rate is significantly improved. This indicates that by simultaneously controlling the proportion of primary particles with a particle size of less than or equal to 0.3 μm in the first primary particles per unit area of the coating surface, the weight proportion of fluoroethylene carbonate in the electrolyte, and the weight ratio of cyclic ethylene carbonate to fluoroethylene carbonate, the high-temperature cycle impedance of the battery is reduced and the high-temperature long-cycle performance of the battery is improved.
[0243] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A battery, characterized in that, The battery includes a separator, a negative electrode, a positive electrode, and an electrolyte. The separator includes a carrier layer and coatings on both sides of the carrier layer. The coating corresponding to the negative active layer in the negative electrode is composed of first particles, and the coating corresponding to the positive active layer in the positive electrode is composed of first particles and second particles. The first particles are composed of a first polymer, which is an ester-containing polymer. Within a 100μm × 100μm area on the surface of the coating, the number of primary particles with a particle size less than or equal to 0.3μm accounts for 0.01%-4% of the total number of primary particles. The electrolyte includes cyclic carbonate and fluoroethylene carbonate, and the weight ratio of the cyclic carbonate to the fluoroethylene carbonate is (0.2-1.5):
1.
2. The battery according to claim 1, wherein, The second particle comprises a fluoropolymer, and the battery satisfies the following relationship: 1≤d1 / d2≤25, where d1 is the average particle size of the secondary particles of the second particle, and d2 is the Dv95 of the first particle; And / or, the average particle size d1 of the secondary particles of the second particle is 2μm-15μm; And / or, the second particle accounts for 0%-90% of the mass of the coating; And / or, the first particle accounts for 10%-100% of the mass of the coating; And / or, the Dv95 of the first particle is 0.5μm-5μm.
3. The battery according to claim 2, wherein, The monomers forming the fluoropolymer include one or more of vinylidene fluoride, tetrafluoroethylene, hexafluoroethylene, and hexafluoropropylene; And / or, the fluoropolymer includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride, polyhexafluoropropylene, fluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.
4. The battery according to claim 1, wherein, The thickness of the coating is 0.5μm-5μm; And / or, the coating has a coverage of 8%-100% on the surface of the carrier layer; And / or, the first particles are arranged in a stacked manner in the coating; And / or, the negative electrode sheet includes a negative current collector and a negative active layer located on one or both sides of the negative current collector, the negative active layer including a silicon-based material, the silicon-based material including one or more of elemental silicon particles, silicon oxide particles, silicon-carbon composite particles, silicon-nitrogen composite particles and silicon alloy particles; And / or, the positive electrode sheet includes a positive current collector and a positive active layer located on at least one surface of the positive current collector, wherein the positive electrode material in the positive active layer is lithium cobalt oxide.
5. The battery according to claim 1, wherein, The first polymer is an acrylate polymer, and the glass transition temperature of the first polymer is 40℃-75℃; And / or, the weight percentage of ester groups in the coating is 20%-60%; And / or, the monomers forming the first polymer include one or more of methyl methacrylate, butyl acrylate, n-propyl acrylate, octyl acrylate, ethyl methacrylate, isooctyl acrylate, octadecyl acrylate, ethyl acrylate, cyclohexyl acrylate, and 2-hydroxyethyl acrylate. And / or, the first polymer comprises one or more of the following: polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, acrylate-acrylonitrile copolymer, acrylate-ethylene copolymer, acrylate-acrylonitrile-ethylene copolymer, styrene-acrylate monomer-acrylonitrile copolymer, ethylhexyl acrylate-methyl methacrylate copolymer, butyl acrylate-methyl methacrylate copolymer, methyl acrylate-N,N-dimethylacrylamide copolymer, ethyl acrylate-2-(diethylamino)ethyl acrylate copolymer, ethyl acrylate-N,N-diethylacrylamide copolymer, and ethyl acrylate-2-(diethylamino)ethyl acrylate.
6. The battery according to any one of claims 1-5, wherein, At 80°C, after the diaphragm is compressed for 0.5 hours under a pressure of 2 MPa, the compression rate of the diaphragm is 10%-50%. And / or, after the diaphragm is baked at 80°C for 2 hours, the porosity of the diaphragm is 30%-60%.
7. The battery according to any one of claims 1-5, wherein, The cyclic carbonates include ethylene carbonate and / or propylene carbonate; And / or, the cyclic carbonate in the electrolyte accounts for 5%-50% by weight; And / or, the carrier layer includes a substrate layer and a heat-resistant layer located on one or both surfaces of the substrate layer, the heat-resistant layer including third particles and an adhesive, wherein the weight ratio of the third particles to the adhesive is (30%-99%):(70%-1%).
8. The battery according to claim 4, wherein, The average particle size of the silicon-carbon composite particles is 5μm-12μm; And / or, the degree of graphitization of the silicon-carbon composite particles is 0-0.85; And / or, the sphericity of the silicon-carbon composite particles is 0.6-1.
9. The battery according to claim 7, wherein, The Dv10 of the third particle is 0.01μm-1.5μm; And / or, the thickness of the heat-resistant layer is 0.2μm-5μm; And / or, the thickness of the substrate layer is 2μm-10μm; And / or, the porosity of the substrate layer is 25%-70%.
10. The battery according to claim 7, wherein, The third particle comprises boehmite, alumina, barium sulfate, magnesium oxide, magnesium hydroxide, silicon dioxide, tin dioxide, titanium dioxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, cerium oxide, zirconium titanate, barium titanate, magnesium fluoride, 1,3,5-triazine-2,4,6-triamine, melamine thiocyanate, melamine cyanurate, symmetrical triaminotriazine, and 2-(4-bromophenyl)-4,6-dimethyl-1,3, One or more of the following: 5-triazine, 1-(4,6-diamino-1,3,5-triazine-2-yl)guanidine, 2,4-diamino-6-dimethylamino-1,3,5-triazine, cyanuric chloride, 2,4,6-tris(2-pyridyl)triazine, 2,4,6-triphenyl-1,3,5-triazine, tris(tribromophenoxy)triazine, 2-amino-4,6-methoxy-1,3,5-triazine, uracil, cytosine, and lithium aluminum titanium phosphate; And / or, the adhesive comprises one or more of the following polymers: polyvinyl alcohol, styrene-butadiene rubber, ethylene-vinyl acetate copolymer, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, ethyl polyacrylate, polyacrylic acid, polyvinyl acetate, polyacrylate, polyurethane, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), and copolymers derived from the above polymers; And / or, the composition of the substrate layer includes one or more of the following polymer derivatives: polyolefin, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl chloride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyethylene terephthalate, polybutylene terephthalate, poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), and poly(m-phenylene isophthalamide).